Exploration of the origin of the 2020 X-ray outburst in OJ 287. Issue 2 (2nd August 2022) - Huang, Shifeng; Hu, Shaoming; Yin, Hongxing; Chen, Xu; Alexeeva, Sofya; Jiang, Yunguo
ABSTRACT: Research into OJ 287 has been ongoing for many years. In 2020 April–June, this source underwent the second highest X-ray outburst (second only to the 2016–2017 outburst) and the mechanism of this outburst is still under debate. In this paper, we discuss two scenarios to explore the origin of the outburst: an after-effect of a black hole–disc impact and a tidal disruption event (TDE). We present the weak correlations of the spectral index versus X-ray flux and the hardness ratio (HR) versus the soft X-ray flux during the outburst, and these features are different from the case in the quiescent state. The correlations are compared with those of the 2016–2017 outburst with the highest X-ray flux in monitoring history. Analysis of the outbursts in 2016–2017 and 2020 shows that the expected time of the X-ray outburst, based on the theory of the after-effect of the black hole–disc impact and the estimation of available data, is inconsistent with historical observations. The soft X-ray spectra, the barely temporal evolution of colour, and the evolution of the HR mean that the 2020 outburst shares similar features with the 2016–2017 outburst, which was considered as a possible candidate for a TDE. Additionally, we find that the predictions of full TDEs ( t −5/3 ) and partial TDEs ( t −9/4 ) for the soft X-ray decay light curve are well fitted. Our analysis suggests that the 2020 outburst in OJ 287 is probably related to the TDE candidate.